The Caribbean Court of Justice : audited financial statements for the year ended December 31, 2017 (BDO Port of SpainTT, 2018)
Presents the audited financial statements of the CCJ which comprise the statement of financial position as at December 31, 2017 and the statement of comprehensive income, statement of changes in accumulated fund, and statement of cash flows for the year then ended, and notes to the financial statements, including a summary of significant accounting policies.
Keywords: FINANCIAL STATEMENTS